2016
DOI: 10.22146/jkr.12640
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Konseling Laktasi Pada Ibu Hamil Trimester Iii Terhadap Pemberian Prelaktal Bayi Baru Lahir

Abstract: Background: Exclusive breastfeeding's rate in Indonesia is still low. One of the causes of this failure is the prelacteal feeding in infants' early life. Prelacteal feeding can cause the infants reluctance to suckle their mothers' breasts, diarrhea, allergy, ear infections and respiratory disorders in infants. One of the efforts to prevent prelacteal feeding is providing lactation counselingto women in the third trimester of pregnancy. Objective: To assess the impact of lactation counseling to women in the thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 1 publication
0
1
0
1
Order By: Relevance
“…The success of lactation counseling is influenced by several factors, namely: lack of acceptance of mothers with breastfeeding problems, lack of health services in overcoming issues of public health status, beliefs or cultural values in society, and environmental factors that do not support. [24][25][26] However, this study was strengthened by research by Ambarwati et al 23 that the control group showed no difference in breastfeeding success before and after being given counseling. The cause was the lack of knowledge and motivation of breastfeeding mothers.…”
Section: Discussionmentioning
confidence: 88%
“…The success of lactation counseling is influenced by several factors, namely: lack of acceptance of mothers with breastfeeding problems, lack of health services in overcoming issues of public health status, beliefs or cultural values in society, and environmental factors that do not support. [24][25][26] However, this study was strengthened by research by Ambarwati et al 23 that the control group showed no difference in breastfeeding success before and after being given counseling. The cause was the lack of knowledge and motivation of breastfeeding mothers.…”
Section: Discussionmentioning
confidence: 88%
“…Terdapat perbedaan pengetahuan ASI dan keterampilan praktik pemberian ASI sebelum dan sesudah dilakukan program pendampingan pada kelompok sasaran [9]. Perbandingan ibu yang diberikan konseling laktasi pada kehamilan trimester ketiga 1,69 kali memberikan kemungkinan lebih besar tidak memberikan prelaktal (makanan tambahan) jika dibandingkan dengan ibu yang tidak dibekali konseling laktasi [10].…”
Section: Hasil Dan Pembahasanunclassified